Post‐progression survival is highly linked to overall survival in patients with non‐small‐cell lung cancer harboring sensitive EGFR mutations treated with first‐line epidermal growth factor receptor‐tyrosine kinase inhibitors. Issue 12 (8th October 2019) - Imai, Hisao; Kaira, Kyoichi; Mori, Keita; Kotake, Mie; Mitani, Masumi; Kawashima, Naoko; Hisada, Takeshi; Minato, Koichi
Abstract: Background: In patients with epidermal growth factor receptor ( EGFR )‐mutated advanced non‐small‐cell lung cancer (NSCLC), epidermal growth factor receptor‐tyrosine kinase inhibitor (EGFR‐TKI) treatment has shown a good response. Subsequent treatments jeopardize the ability to determine the effect of first‐line chemotherapy on overall survival (OS). Therefore, using patient‐level data, we aimed to study the associations of progression‐free survival (PFS) and post‐progression survival (PPS) with OS after first‐line EGFR‐TKI treatment in patients with EGFR ‐mutated NSCLC. Methods: Between November 2006 and December 2016, we analyzed 92 patients with EGFR ‐mutated NSCLC treated with first‐line EGFR‐TKI. The correlations of PFS and PPS with OS were analyzed for each patient. Results: Spearman's rank correlation and linear regression analyzes showed that PPS correlated highly with OS ( r = 0.85, P < 0.05, R 2 = 0.75), whereas PFS correlated weakly with OS ( r = 0.76, P < 0.05, R 2 = 0.50). The best responses after first‐line and second‐line treatments were significantly associated with PPS. Conclusions: PPS has a higher impact on OS than PFS in patients with EGFR ‐mutated NSCLC treated with first‐line EGFR‐TKIs. These outcomes suggest that the OS in this patient group may be affected by treatments following first‐line chemotherapy; however, this remains to be verified in prospective trials.